2009
DOI: 10.1002/ajh.21334
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of β‐catenin and topoisomerase IIα in de novo acute myeloid leukemia

Abstract: The Wnt/b-catenin signaling is important for controlling self-renewal of hematopoietic stem cells and its constitutive activation has recently been documented in a significant proportion of acute myeloid leukemia (AML) cases. Topoisomerase IIa (Topo IIa) is a marker of cell proliferation and a crucial target for anthracycline cytotoxicity, the mainstay of management employed in AML. We retrospectively investigated the prognostic roles of b-catenin and topo IIa in a cohort of 59 patients with newly diagnosed AM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 36 publications
2
19
0
1
Order By: Relevance
“…In a survival analysis, they demonstrated that β-catenin appeared as a new independent prognostic factor predicting poor event-free survival and shortened overall survival (23). A similar report was recently published by another group, in which analysis of a cohort of 59 AML patients, demonstrated that high expression of β-catenin is related to shortened overall survival (24).…”
Section: Discussionmentioning
confidence: 54%
“…In a survival analysis, they demonstrated that β-catenin appeared as a new independent prognostic factor predicting poor event-free survival and shortened overall survival (23). A similar report was recently published by another group, in which analysis of a cohort of 59 AML patients, demonstrated that high expression of β-catenin is related to shortened overall survival (24).…”
Section: Discussionmentioning
confidence: 54%
“…Either change can result in the activation of their downstream genes, including oncogene c-MYC and cyclin D1 to promote neoplastic growth (34)(35)(36)(37). Aberrant expression of b-catenin, which plays a central role in Wnt signaling, is associated with a poor prognosis in patients with acute myeloid leukemia (38,39). Interestingly, a recent study showed that a subgroup of patients with acute lymphoblastic leukemia was associated with a poor prognosis when the leukemia cells express CD1d (40).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, genetic or pharmacological suppression of b-catenin expression inhibited leukemogenic transformation mediated by MLL fusions or Hoxa9/MEIS1, revealing its essential function in leukemic transformation [31 & ,32 && ]. In human AML, elevated b-catenin expression is also associated with high relapse rate and poor overall survival [33,34]. Elevated expression of b-catenin enhanced blastreplating efficiency [33].…”
Section: The Canonical Wnt/b-catenin Pathway In Acute Myeloid Leukemiamentioning
confidence: 99%